HIGH-PERFORMANCE SIMULATIONS OF POPULATION-GENETIC PROCESSES IN BACTERIAL COMMUNITIES USING THE HAPLOID EVOLUTIONARY CONSTRUCTOR SOFTWARE - Z. S. Mustafin; Yu. G. Matushkin; S. A. Lashin (Вавиловский журнал генетики и селекции)
Three high-performance versions of the Haploid Evolutionary Constructor program are presented (http://evol-constructor.bionet.nsc.ru). The software was designed for simulating the functioning and evolution of microbial communities. These high-performance versions are to be run on systems with shared and distributed memory, using CPU and/or GPU. Almost linear acceleration has been achieved on clusters and multi-core CPU. On GPU systems, the simulation time was reduced to several minutes (dozens of hours on CPU).